The role of nonstandard work hours in maternal caregiving for young children - Rachel Connelly; Jean Kimmel (Institute for the Study of Labor (IZA), 2007)
This paper examines the effect of the timing of mothers' daily work schedules on the amount of maternal caregiving she engages in on that same day. We look at total caregiving time on weekdays, early morning and evening caregiving time on weekdays, and total caregiving time on weekends. Since the timing of employment is, in part, a choice made by mothers, which is sometimes explicitly related to caregiving concerns, we argue that the decision to work nonstandard hours must be modeled jointly with its effect on caregiving time. Using an endogenous switching model, we examine the importance of demographic, spatial, and economic factors in mothers' time choices distinctly by nonstandard work status. We find that the effect of additional children in the household has a larger effect on caregiving time for standard time workers than nonstandard workers, both weekdays and weekend. Especially important is the additional hours of evening care given by those with a young school-aged child if the mother works standard hours only, but no additional hours of evening care given by those with a young school-age child if the mother works any time after 6 pm. Being married reduces early morning and evening caregiving only if the mother is working in the early morning or the evening. In households with mothers working standard hours only, being married has no effect on mothers' caregiving time. Finally, higher working mothers' wages are associated with increased caregiving minutes both during the week and on the weekend only for those mothers who perform some of their paid employment during nonstandard hours.
Keywords: 330; Time use; nonstandard work hours; caregiving; Kinderbetreuung; Mütter; Arbeitszeitflexibilisierung; Zeitbudgetforschung; USA